Clinical Characteristics and Admission Patterns of Hospitalized Children in a Pediatric Department at Tobruk Medical Center: Retrospective Study (Derna Academy Journal for Applied Sciences, 2026)
Background: The neonatal period is the most vulnerable stage of life. Although the perinatal and neonatal phases are short, they represent some of the most critical moments in human development. Objectives: The goal of this study is to determine the patterns of pediatric hospital admissions, identify the types of illnesses and their distribution across different age groups at Tobruk Medical Center. Methods: A descriptive retrospective study was conducted in the Pediatric Department of Tobruk Medical Center from January to April 2025, including children aged 1 month to 15 years. Data analysis was performed using SPSS to assess relationships between variables. Results: Respiratory diseases were the most common reason for admission (25.2%), followed by central nervous system disorders (17.5%), with neonatal sepsis (13.7%) and neonatal jaundice (11.1%) identified as the leading individual diagnoses. Admission patterns differed significantly across age groups, demonstrating a strong association between age and diagnostic category (χ² = 210.816, df = 36, p < 0.001; Cramér’s V = 0.410), which reflects distinct age-related clinical profiles. Conclusion: Admissions were mainly among infants and young children, with respiratory and neonatal conditions predominating, and most patients presenting directly to the hospital. These findings underscore the need for effective assessment and referral systems to manage pediatric admissions efficiently.